Stabilizing Si/graphite composites with Cu and in situ synthesized carbon nanotubes for high-performance Li-ion battery anodes. Issue 6 (8th May 2018) - Xu, Tianjun; Lin, Ning; Cai, Wenlong; Yi, Zheng; Zhou, Jie; Han, Ying; Zhu, Yongchun; Qian, Yitai
Abstract : A Si/graphite/Cu–CNT composite was prepared using a mechanical ball-milling method followed by a Cu-catalyzed chemical vapor deposition process. Abstract : The low theoretical capacity (372 mA h g −1 ) of the conventional commercial graphite anode limits its widespread applications, so it is urgent to prepare novel high-capacity anodes. Here, as a modification of graphite, a Si/graphite/Cu–carbon nanotube composite is prepared using a scalable and low-cost method including ball-milling of commercial micro-sized Si, Cu and graphite, followed by in situ growth of carbon nanotubes catalyzed by Cu. The Si, Cu and graphite are homogeneously mixed in the composite. Meanwhile, in situ synthesized carbon nanotubes are able to further cross-link all components tightly and construct a three-dimensional conductive network. As an anode for lithium-ion batteries, the as-prepared composite presents a reversible capacity of 738.3 mA h g −1 with a capacity retention of 87.6% after 100 cycles at 0.2 A g −1 and a reversible capacity of 538 mA h g −1 after 200 cycles at 0.5 A g −1, which is much better than those of Si/graphite and Si/graphite/Cu composites. The enhanced electrochemical performance of the Si/graphite/Cu–carbon nanotube composite is mainly attributed to the graphite, Cu and carbon nanotube contents which are synergistically beneficial for improving the structural integrity and electrical conductivity of the composite.